2017
DOI: 10.1039/c7sc04098a
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal room temperature phosphorescence of purely organic boron-containing compounds: the relationship between the emissive behaviorand the molecular packing, and the potential related applications

Abstract: Long-lived RT phosphorescence was achieved with a series of organic boron-containing compounds due to the rigid conformation and effective π–π stacking in the solid states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
120
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(122 citation statements)
references
References 35 publications
1
120
0
1
Order By: Relevance
“…Strong phosphorescence emissions around 600 nm were recorded for both S‐2CN and S‐2I, further confirming the red RTP origins in hgDCs and also indicating efficient S 1 →T 1 ISC processes in these two β‐iminoenamine‐BF 2 compounds. As strong phosphorescence was recorded at low temperature, it was reasonable to guess that the absence of RTP in solution and powder crystals is attributed to the rotation, vibration and collision triplet relaxations . Considering the highly freedoms of 4‐cyanophenyl and 4‐iodophenyl groups, it's hopeful to switch on RTP by restricting the motions of these two active substituents .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Strong phosphorescence emissions around 600 nm were recorded for both S‐2CN and S‐2I, further confirming the red RTP origins in hgDCs and also indicating efficient S 1 →T 1 ISC processes in these two β‐iminoenamine‐BF 2 compounds. As strong phosphorescence was recorded at low temperature, it was reasonable to guess that the absence of RTP in solution and powder crystals is attributed to the rotation, vibration and collision triplet relaxations . Considering the highly freedoms of 4‐cyanophenyl and 4‐iodophenyl groups, it's hopeful to switch on RTP by restricting the motions of these two active substituents .…”
Section: Figurementioning
confidence: 99%
“…As strong phosphorescence was recorded at low temperature, it was reasonablet og uess that the absence of RTP in solution andp owder crystals is attributed to the rotation, vibration and collisiont riplet relaxations. [16] Considering the highly freedoms of 4-cyanophenyl and 4-iodophenylg roups, it's hopeful to switch on RTP by restricting the motionso ft hese two active substituents. [9] To reveal the PL mechanism for S-2CN/IÀPhÀNH 2 and S-2I/IÀPhÀNH 2 hgDCs, we furtherp erformed theoretical calculations by using the ONIOM (B3LYP/GENECP: UFF) approach to optimize the geometry (see the Supporting Information for details).…”
mentioning
confidence: 99%
“…In 2017, Li and co‐workers reported that a series of boron‐containing phosphors exhibited long‐lived RTP in the crystalline state (Figure a) . Through extensive experiments, they concluded that the persistent RTP properties benefitted from hydrogen bonds between these arylboronic acids.…”
Section: Enhanced Rtp Through Intermolecular Hydrogen Bondingmentioning
confidence: 99%
“…[3c] In 2017, Li andc o-workersr eported that as eries of boroncontaining phosphors exhibited long-lived RTP in the crystalline state (Figure 7a). [38] Through extensive experiments, they concluded that the persistent RTP properties benefitted from hydrogen bonds between these arylboronic acids. On one hand, these strongi ntermoleculari nteractions restricted the phosphors in ar igid environmentt od ecrease the rapid rate of triplet nonradiative decay.O nt he other hand, as shown in Figure 7b,the stacking mode that contributed to hydrogen bonding also facilitated p-p stacking interactions,w hich stabilize the triplet states.…”
Section: Enhanced Rtp Through Intermolecular Hydrogen Bondingmentioning
confidence: 99%
See 1 more Smart Citation